Allocative Efficiency of Production Input of Pacific White Shrimp Farming in Grabag District, Purworejo Regency, Central Java - Gama Dian Nugroho; Masyhuri Masyhuri; Irham Irham (JURNAL PERIKANAN DAN KELAUTAN, 2018)
This study aims to determine the factors that affect the productivity of white shrimp farming business, allocative efficiency and profit of white shrimp farming in Grabag District, Purworejo Regency, Province of Central Java. The method used in this study was descriptive analysis. Selection of the study sample was done by purposive sampling that was farmer of white shrimp in Grabag District with total respondent in this study were 51 people. Production variables in this study were shrimp seed, feed, probiotics, lime, labour, farmer age, farmer education and farmer's experience. The analytical method used in this study was linear regression from Cobb-Douglas production function, to determine the factors that influenced the productivity of white shrimp farming business so that it could analyze the allocative efficiency, besides the profit analysis. The result of the analysis showed that: (1) the factors that influenced the productivity of white shrimp farming were feed, probiotics and farmers' experience, (2) the use of feed production and probiotic factor was not allocatively efficient so its use should be increased, (3) Average profit of white shrimp farming business was 996.116.057 IDR with average of pond area of 7.011,76 m2 / farmer so that average of each farmer got profit 142.063,63 IDR/m2/year.